Estimation of seasonality and prevalence of the isopod parasite Ceratothoa oestroides, Risso, 1836, in Greece - VAGIANOU (ΣΤ. ΒΑΓΙΑΝΟΥ), St.; BITCHAVA (Κ. ΜΠΙΤΧΑΒΑ), C.; YAGNISI (Μ. ΓΙΑΓΝΙΣΗ), M.; ATHANASSOPOULOU (Φ. ΑΘΑΝΑΣΟΠΟΥΛΟΥ), F. (Journal of the Hellenic Veterinary Medical Society, 2017)
The aim of the present study was the investigation of the seasonality of isopod parasite Ceratothoa oestroides (Risso, 1836), in two different farms, in the region of Chios and in the region of Astakos. In each area, in total 80 sea bass and 80 gilthead sea breams in each sampling were examined. One seasonal sampling in each farm for the two species was taken and four samplings were performed in a year for the two species. The samples were collected by the same cages and their medium weights as well as themedium temperatures per stockfarming were recorded. In gilthead sea bream the isopod parasite Ceratothoa oestroides was found only in the region of Astakos at a prevalence of 31,2%, which presented a maximum value during the summer months. In sea bass the parasite was found in the two regions (prevalence 33,75% and 55,25%, respectively). It was observed that the rate of pollution in Astakos was higher in spring, whereas in Chios the prevalence was higher in summer. Finally, the young individuals of stage of puliiII parasitise were what caused serious alterations and finally the death of mainly young fishes of gilthead sea bream (Spams aurata)and bassfish (Dicentrarchus labrax). The adults hosts appearred that they were not influenced particularly by the presence of parasitises.